Genome-wide association study identifies variation at 6q25.1 associated with survival in multiple myeloma - Johnson, David C.; Weinhold, Niels; Mitchell, Jonathan S.; Chen, Bowang; Kaiser, Martin; Begum, Dil B.; Hillengaß, Jens; Bertsch, Uta; Gregory, Walter A.; Cairns, David; Jackson, Graham H.; Försti, Asta; et al. (Nature Communications, 2016)
The prognosis of multiple myeloma patients varies widely. Here, to identify genetic factors associated with differing prognoses, the authors carried out a meta-analysis of four genome-wide association studies and identified a risk variant associated with survival interval.
Gesehen am 06.05.2020